FORMULATION AND EVALUATION OF REPAGLINIDE PATCHES FOR TRANSDERMAL DRUG DELIVERY - RAHUL SHIVAJIRAO SOLUNKE,; PRAVEEN D. CHAUDHARI, (International Journal of Pharma and Bio Sciences, 2017)
Transdermal drug delivery is an alternative route for systemic drug delivery which minimizes the absorption and increases the bioavailability. Repaglinide is an Anti-Diabetic drug with a shorter half-life (1 hr), low bioavailability (56 %) undergoes extensive first pass metabolism are required to maintain the therapeutic level it has chosen as transdermal drug delivery system. The present study was to formulate and evaluate transdermal drug delivery system of Repaglinide using polymers such as HPMC & Eudragit RLPO by solvent casting technique. The prepared formulations were evaluated for different physicochemical characteristics like Weight Variation, Folding Endurance, Flatness, pH of patches, % Moisture Content, % Moisture uptake, % Elongation, % Drug Content & % Drug Release. The drug release characteristics of the formulation were studied in-vitro by using artificial semi-permeable membrane. The in-vitro drug release plot has shown that the drug release followed zero order kinetics & Higuchi model, which was evidenced from the regression values. Based on the drug release and physicochemical values obtained from the formulation F2 is considered as an optimized formulation which shows higher percentage of drug release (98.20±0.27 % at 14 hour) with diffusion mediated mechanism.